Pelatihan Pengolahan Minyak Biji Bunga Matahari (Helianthus Annus L.) Menjadi Massage Oil: Training on Processing Sunflower Seed Oil (Helianthus annus L.) into Massage Oil - Dewi Perwito Sari; Rahayu, Asti; Mukti, Asri Wido; Hardani, Prisma Trida; Mukti, Ria Andriani; Purbosari, Ira; Pramushinta, Intan Ayu Kusuma; Andarwulan, Setiana; Sopandi, Tatang; Wijayati, Prasmita Dian; Mukhtar, M. Nushron Ali Mukhtar; Fatmawati; Ambarwati, Nadya; Sinulingga, Amanda Safithri; Amalia, Sri Hidayati; Framono, Indra Dwi (J.Abdimas: Community Health, 2024)
Massage treatment is part of traditional health services which can provide a stimulating and relaxing effect, improve the blood and lymph circulation system and strengthen other body systems, intended to improve health and fitness. Massage treatments generally use massage oil containing essential oils as aromatherapy. The use of essential oils in aromatherapy, especially through massage treatments, must be mixed with carrier oil in the form of vegetable oil such as sunflower seed oil. Pengalangan village is a sunflower agrotourism village with great sunflower potential but the results of sunflower cultivation are still less than optimal and are limited to sunflower seed food. Therefore, the team provides an Eco-preneurship solution with an effort to increase the selling value of the results of processing sunflower seeds in the form of oil to be processed into massage oil. This effort was carried out by providing material using the lecture method and continued with training in making massage oil for PKK cadres and village residents as participants. The end of this activity showed an increase in participants' knowledge by 16.8%, as well as an increase in participants' skills in making massage oil products independently.